Smart water-based system for healthy living / Aliya Najiha Amir - Amir, Aliya Najiha (Universiti Teknologi MARA, Kedah, 2019)
Since the water quality from water resources like home water filtration system and tap water are commonly unknown, the consumer may exposed with the risk of drinking contaminated water. The problem arise when there are many water borne disease cases were reported. At the same time, the conventional method of performing water quality assessment is time consuming, labor intensive and lack of real time information. Current study suggests to perform regular monitoring of water quality. Therefore, the objective of this project is to implement IoT application in monitoring water quality. The scope of study covers the potential water borne disease cause by poor water quality as well as the application of IoT in monitoring water quality. The proposed project focuses on implementing IoT technologies that would enable the development of real-time water quality monitoring system. The propose approach would replace the traditional method of doing assessment of water quality.